Exploring Primary School Principals’ Experiences in Supporting Teachers Living with HIV/AIDS in Gauteng Province - Sedibe, Mabatho; Matjeke, Herman (Richtmann Publishing, 2022)
The study highlighted the exploration and description of the primary school principals’ experiences in supporting teachers living with HIV/AIDS in Gauteng Province, South Africa. As a result of qualitative research method through literature review and interviews which were used in collecting data from the primary school participants, the results revealed that at primary level, school principals still lack the experiences in as far as supporting their teachers living with HIV/AIDS in Gauteng province is concerned. Received: 7 October 2021 / Accepted: 25 November 2021 / Published: 5 January 2022